Disparities in HIV/STI burden and care coverage among men and transgender persons who have sex with men in Nairobi, Kenya: a cross-sectional study. Issue 12 (30th December 2021) - Smith, Adrian D; Fearon, Elizabeth; Kabuti, Rhoda; Irungu, Erastus; Kungu, Mary; Babu, Hellen; Nyabuto, Chrispo; Muthoga, Peter; Weatherburn, Peter; Bourne, Adam; Kimani, Joshua
Abstract : Objectives: The study aimed to estimate the prevalence of, and associations, with HIV and metrics of HIV care engagement in a representative population of gay, bisexual and other men who have sex with men (GBMSM) and transgender persons (TP) who have sex with men (GBMSM/TP) Setting: Urban districts of Nairobi, Kenya. Design: Cross-sectional. Participants: 608 eligible participants were identified through respondent-driven sampling over 19 waves of recruitment arising from ten seeds between May and December 2017. Inclusion criteria were: age >18 years; Nairobi residence; male sex assignment at birth or current identification as male, and recent consensual sex with male partners. Exclusion criteria were: missing or invalid recruitment coupon; repeat registration; intoxication at study visit. Primary and secondary outcome measures: HIV status measured using Determine Alere HIV 1/2 and First Response HIV 1–2.0 and GeneXpert HIV-1 Qual. Self-reported metrics of HIV status awareness, antiretroviral use and objective quantification of viral suppression using GeneXpert HIV-1 VL. Results: 26.4% (286/618) were HIV positive of whom 76.6% were status aware, 65.3% were on antiretroviral therapy (ART), and 47.4% were virally suppressed (<50 copies/mL). Participants 18–22 years were less likely to be status aware, be receiving ART or to have achieved viral suppression. Mean log viral load was 3.14 log higher in 18–22 years compared with older participants. Bacterial sexually transmitted infections were common at both urethral and rectal sites and most infections were asymptomatic by self-report (rectal 82.2%, urethral 82.3%). Conclusions: Engagement in the HIV diagnosis and care cascade among GBMSM/TP in Nairobi is markedly better than in most sub-Saharan African countries, yet falls short of achievements for the general population in Kenya and for GBMSM in high income settings. Young GBMSM/TP are least well served by the current configuration of adult key population services, and programmes should identify and address the sexual, social and developmental needs of adolescent and young key populations.